2013
DOI: 10.1016/j.biochi.2013.03.001
|View full text |Cite
|
Sign up to set email alerts
|

ADAM9 silencing inhibits breast tumor cell invasion in vitro

Abstract: ADAM9 (A Disintegrin And Metalloproteinase 9) is a member of the ADAM protein family which contains a disintegrin domain. This protein family plays key roles in many physiological processes, including fertilization, migration, and cell survival. The ADAM proteins have also been implicated in various diseases, including cancer. Specifically, ADAM9 has been suggested to be involved in metastasis. To address this question, we generated ADAM9 knockdown clones of MDA-MB-231 breast tumor cells using silencing RNAs t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…Furthermore, the deficiency of some ADAMs, such as ADAM9, ADAM15 and ADAM17 resulted in decreased tumor cell growth in mice models of metastasis [11,12]. In addition, a recent study from our group showed that ADAM9 silencing inhibited matrigel invasion of MDA-MB-231 metastatic breast tumor cells (about 70%) [16].…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…Furthermore, the deficiency of some ADAMs, such as ADAM9, ADAM15 and ADAM17 resulted in decreased tumor cell growth in mice models of metastasis [11,12]. In addition, a recent study from our group showed that ADAM9 silencing inhibited matrigel invasion of MDA-MB-231 metastatic breast tumor cells (about 70%) [16].…”
Section: Discussionmentioning
confidence: 88%
“…These results strongly suggest a key role for ADAM9 in the regulation of MMP2 expression. However, despite the increase in MMP2 expression, siADAM9 inhibited MDA-MB-231 cells invasion into matrigel by approximately 70% [16].…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations